2007
DOI: 10.1186/1465-9921-8-65
|View full text |Cite
|
Sign up to set email alerts
|

In vitro metabolism of beclomethasone dipropionate, budesonide, ciclesonide, and fluticasone propionate in human lung precision-cut tissue slices

Abstract: Background: The therapeutic effect of inhaled corticosteroids (ICS) may be affected by the metabolism of the drug in the target organ. We investigated the in vitro metabolism of beclomethasone dipropionate (BDP), budesonide (BUD), ciclesonide (CIC), and fluticasone propionate (FP) in human lung precision-cut tissue slices. CIC, a new generation ICS, is hydrolyzed by esterases in the upper and lower airways to its pharmacologically active metabolite desisobutyryl-ciclesonide (des-CIC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 30 publications
2
30
0
Order By: Relevance
“…In vitro studies in human tissue and in vivo studies in rats have reported that des-CIC forms reversible conjugates with fatty acids, which are pharmacologically inactive and do not bind to the glucocorticoid receptor [7,[13][14][15]. The findings regarding the metabolism of CIC derived from in vitro and animal studies have yet to be confirmed by in vivo studies in human subjects.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…In vitro studies in human tissue and in vivo studies in rats have reported that des-CIC forms reversible conjugates with fatty acids, which are pharmacologically inactive and do not bind to the glucocorticoid receptor [7,[13][14][15]. The findings regarding the metabolism of CIC derived from in vitro and animal studies have yet to be confirmed by in vivo studies in human subjects.…”
mentioning
confidence: 75%
“…These in vivo findings confirm the two major metabolic pathways of ciclesonide in the human lung: the rapid, on-site conversion of ciclesonide to des-CIC and the conjugation of des-CIC with fatty acids, in particular oleic acid. Such findings have previously been shown in vitro in human tissue and in vivo in animals [13][14][15]. • • ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ therefore, a slight offset for different time-points in these patients was used for better illustration.…”
Section: Discussionmentioning
confidence: 99%
“…The four compounds produced were two monopropionates, that is, beclomethasone 17-monopropionate (2) and beclomethasone 21-monopropionate (3), one epoxy (5), and one depropionated derivative (4). Compound (4) was already reported as pharmacologically inactive, and compound (2) was pharmacologically active (Nave, Fisher, McCracken, 2007), whereas compound (3) was reported as pharmacologically inactive compound (Würthwein, Rohdewald, 1990). It is expected that the new metabolites formed may have more anti-inflammatory activity; better therapeutic profile, safety, and efficacy; and least resistance and can be employed in the treatment of asthma as that of the parent compound.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of these metabolites is less than 1% of that of the parent compound, and they do not contribute further to the therapeutic effect of budesonide (Silverman & Otley, 2011). In vitro studies of the phase II metabolism of budesonide have demonstrated that it undergoes sulfation by cytosolic sulfotransferase enzyme 1A1 (Meloche et al, 2002); studies in lung tissue slices have also demonstrated the formation of fatty acid esters from budesonide (Nave et al, 2007). Budesonide is eliminated in the urine (60%) and faeces (40%) as metabolites (US Food and Drug Administration, 2009).…”
Section: Introductionmentioning
confidence: 99%